Focus on Epithelialized Palatal Grafts. Part 2: Implant Site Development. Issue 3 (3rd May 2019) - Berridge, Joshua P.; Johnson, Thomas M.; Erley, Kenneth J.; Hill, Richard B.; Lane, Jonathan D.; Schlam, Kimberly K.; Dunham, Daniel D.; Miller, Preston D.
Abstract : Introduction: The epithelialized palatal graft (EPG), introduced in 1963, has persisted as the gold standard for gingival augmentation, and in the present era, mucosal augmentation around dental implants has become an important concern. A limited body of evidence suggests peri‐implant mucosal augmentation may favorably impact bone and mucosal stability and peri‐implant health under some circumstances. Although more contemporary procedures for peri‐implant mucosal augmentation are often preferred based on convenience and esthetic considerations, EPG augmentation at dental implant sites is distinguishable from methods which do not deepen the vestibule and eliminate unfavorable superficial soft tissue. Implant sites augmented with EPG are qualitatively distinct from sites augmented using other methods. Case Series: Seven generally healthy patients received EPG augmentation before dental implant placement, at implant placement, before implant uncovering, or after implant uncovering. In each case, the patient exhibited a favorable zone of attached peri‐implant mucosa following treatment. Conclusions: Reliable mucosal augmentation with EPG is achievable at multiple phases in the course of dental implant therapy. EPG augmentation offers distinct clinical advantages and may be preferable to other mucosal augmentation strategies at some dental implant sites.